Identification of key genes associated with anthracnose resistance in Camellia sinensis. - Li-Yi Xu; Jing-Jing Su; Cheng-Kang Zhang; Min Hao; Zi-Wei Zhou; Xiao-Hui Chen; Shi-Zhong Zheng (PLoS ONE)
Anthracnose, a prevalent fungal disease in tea plantations, cause substantial economic losses in tea production. Identifying resistance-associated genes in tea plants is crucial for developing anthracnose-resistant cultivars. This study used eight tea samples with differential anthracnose resistance for phenotypic evaluation, weighted gene co-expression network analysis (WGCNA) of RNA-seq data, WGCNA- QTL co-localization to identify resistance gene, and qRT-PCR validation of candidate genes. in vitro pathogen inoculation assay revealed that the lesion diameters of the eight samples ranged from 1.45 mm to 4.5 mm (ANOVA p = 4.4[Formula: see text]). Using the 'Longjing 43' reference genome, transcriptome assembly achieved 93.9% gene detection rate (31,509/33,557 genes). WGCNA categorized expressed genes into 30 modules with the purple module (containing 907 genes) showing positive trait correlation and the yellow-green module (containing 781 genes) exhibiting negative correlation. Integration of WGCNA and QTL mapping identified two high-confidence candidate genes within LG08 QTL intervals. Both genes exhibited significant upregulation (t-test p < 0.01) in tea plant leaves following Colletotrichum spore inoculation. These findings provide actionable genetic targets for marker-assisted breeding of anthracnose-resistant tea cultivars.